Strongyloides stercoralis coinfection impairs immune control of Mycobacterium tuberculosis in TB infected individuals - Rajamanickam, Anuradha; Dasan, Bindu; Pandiarajan, Arul Nancy; Munisankar, Saravanan; Shanmugam, Sivakumar; Babu, Subash (Frontiers in Immunology, 2026)
BackgroundHelminth co-infection are common in tuberculosis (TB) endemic regions and alter host immunity. However, their impact on immune responses in TB infection (TBI) remains incompletely defined.MethodsWe analyzed QuantiFERON (QFT) supernatants and peripheral blood mononuclear cells (PBMCs) from TBI+Hel+ (S. stercoralis(Ss) infection) (n=15) and TBI+Hel− (n=23) individuals. Cytokine levels were assessed at baseline and following TB antigenic stimulation (TBAg1 and TBAg2), as well as mitogenic stimulation. PBMCs were stimulated with Mycobacterium tuberculosis (M. tuberculosis) H37Rv, and antimycobacterial immunity was assessed using an in vitro mycobacterial growth inhibition assay (MGIA) and multiplex cytokine assays.ResultsWe measured Type 1 (IFN-γ, TNF-α, IL-2), Type 17 (IL-17, IL-22), and proinflammatory cytokines (IL-1α, IL-1β) in QuantiFERON (QFT) supernatants from TBI individuals with (TBI+Hel+) and without (TBI+Hel−) infection. TBI+Hel+ individuals exhibited significantly reduced mycobacterial growth inhibition compared with TBI+Hel− individuals, reflected by higher normalized mycobacterial growth (Δ log10 CFU). Cytokine analysis showed suppression of Th1/Th17 (IFN-γ, IL-2, TNF-α, IL-17, GM-CSF) and proinflammatory cytokines (IL-1α, IL-1β, IL-6, IL-12p70, IL-18) in TBI+Hel+ individuals, alongside increased Th2/regulatory cytokines (IL-4, IL-5, IL-10, IL-13).ConclusionsSs co-infection impairs host antimycobacterial control by skewing TBI immune responses toward Th2/regulatory pathways at the expense of protective Th1/Th17 mechanisms. Our data demonstrate that the importance of considering Ss co-infection into account when developing TB control and vaccination strategies in endemic areas.